High resolution diffusion tensor imaging of the hippocampus across the healthy lifespan. Issue 12 (2nd October 2021) - Solar, Kevin Grant; Treit, Sarah; Beaulieu, Christian
Abstract: The human hippocampus is difficult to image given its small size, location, shape, and complex internal architecture. Structural magnetic resonance imaging (MRI) has shown age‐related hippocampal volume changes that vary along the anterior–posterior axis. Diffusion tensor imaging (DTI) provides complementary measures related to microstructure, but there are few hippocampus DTI studies investigating change with age in healthy participants, and all have been limited by low spatial resolution. The current study uses high resolution 1 mm isotropic DTI of 153 healthy volunteers aged 5–74 years to investigate diffusion and volume trajectories of the hippocampus (whole, head, body, and tail) and correlations with memory. Hippocampal volume showed age‐related changes that differed between head (peaking at midlife), body (no changes), and tail (decreasing across the age span). Fractional anisotropy (FA) and mean, axial, and radial diffusivities (MD, AD, RD) yielded peaks or minima, respectively, at ~30–35 years in all three subregions of the hippocampus. Greater magnitude changes were observed during development than in aging. Age trajectories for both volume and DTI were similar between males and females. Correlations between tests of memory and FA and/or volume were significant in younger subjects (5–17 years), but not in 18–49 year olds or 50–74 year olds. MD was significantly correlated with memory performance in 18–49 year olds, but not in other age groups. Given the diffusion‐weighted image contrast and resolution, head digitations could be examined revealing that the majority of subjects had 3–4 (48%) or 2 (32%) bilaterally with no effect of age. One millimeter isotropic DTI yielded high quality diffusion‐weighted maps of the human hippocampus that showed regionally specific age effects and cognitive correlations along the anterior–posterior axis from 5 to 74 years.